2011
DOI: 10.1007/s13167-011-0126-6
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for the prevention of breast cancer in shift workers

Abstract: The functioning of the human body is regulated by the rhythmical change between rest and activity. The SCN (suprachiasmatic nucleus) is responsible for the central control of the biorhythm and the genetic prediction of the individual chronotype, whereas peripheral time cues such as light, social contacts and times of meals modulate the rhythmical activity of the body. Shift workers suffer from a disruption of the sleep-wake rhythm, insomnia and a lack of melatonin. These factors might trigger the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 23 publications
0
15
0
7
Order By: Relevance
“…Chronotype (or circadian typology), defined as the phase-relationship between one's sleep-wake cycle and formal clock time (Roenneberg et al, 2003), has repeatedly been suggested as a factor that can potentially mediate adaptation to shift work (Erren & Morfeld, 2014;Richter et al, 2011). Individuals with early (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Chronotype (or circadian typology), defined as the phase-relationship between one's sleep-wake cycle and formal clock time (Roenneberg et al, 2003), has repeatedly been suggested as a factor that can potentially mediate adaptation to shift work (Erren & Morfeld, 2014;Richter et al, 2011). Individuals with early (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Frauen weisen ein hohes Risiko für negative, gesundheitliche Konsequenzen der Schichtarbeit auf -insbesondere Frauen über 50 leiden unter Müdigkeit und Schichtarbeiterinnen haben ein Risiko von 28 % für Brustkrebs (18,19). Frauen, die mehr als 20 Jahre Schichtarbeit geleistet haben, haben sogar ein noch weiter erhöhtes Brustkrebsrisiko (20,21…”
Section: Schlafstörungen Bei Schichtarbeitunclassified
“…Detectable stress factors with acknowledged impacts for BC development such as a shift-worker’s job [34]…”
Section: Reviewmentioning
confidence: 99%